(untitled) (International Journal of Engineering and Computer Science, 2017)
Information Extractor is a powerful tool for web data mining and data crawling. Data from web pages. Reform into local file or save to database, post to web server. No need to the web page you are interesting and click what you want to define the extraction task, and run it as you want, or let it run automatically. Data Extraction is act or process of retrieving data out of data sources for further data processing or storage. The import into the intermediate extracting system is thus usually followed by data transformation and possibly the addition of metadata prior to export to another stage in the data workflow. We formally define structured data, the kind of data that we are hoping to extract from the web pages Structured Data is any set of data values conforming to a common type. The Basic Type, denoted by, represents a string of tokens. A token is some basic unit of text.